Relationship Between Spiritual Intelligence and Attitude Toward Fertility and Childbearing in Women - Elnaz FARAJI NESFECHI; Moluk POURALIZADEH; Zahra BOSTANI KHALESI (Archives of Health Science and Research)
Objective: This study aims to determine the relationship between spiritual intelligence (SI) and attitudes toward fertility and childbearing in reproductive-age women.